"Don't Worry, We Are Here for You": Brands as External Source of Control during the Covid-19 Pandemic. Issue 3 (21st July 2021) - Verlegh, Peeter W. J.; Bernritter, Stefan F.; Gruber, Verena; Schartman, Noud; Sotgiu, Francesca
Abstract: The Covid-19 pandemic increases consumers' worries and makes them experience a loss of control over their lives. We investigate how these factors affect the roles that brands play in consumers' lives. Results of a longitudinal survey ( N  = 5, 393) and an online experiment ( N  = 387) show that brands gain relevance and are more firmly included in consumers' self-concepts if consumers experience more worries about Covid-19 and a lack of control. Brands can benefit from this by addressing worries associated with the crisis in their advertisements. This is particularly effective for consumers who express greater worry about the Covid-19 pandemic.